(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
This article reveals the concept and essence of fraud as a threat to the economic security of the organization. The article presents the results of a survey of the B1 group of companies, which discloses information about how many respondents of the organization faced fraud at the enterprise. The article also presents the main types of fraud at the enterprise and tools to combat each of these types.